Internacionalização na pós-graduação stricto sensu em administração - Vigorena, Débora Andrea Liessem (2017)
This study addresses the issue of internationalization of Higher Education and it focuses on evaluating to which extent internationalization efforts are related to results in stricto sensu postgraduate programs of the Administration area in Brazil. The definition of the objective is essential to understand how these programs have been organized in order to progress in internationalization and what were the results obtained based on the indicators suggested by CAPES (Brazilian Federal Agency for Support and Evaluation of Graduate Education) for this process, as well as other indicators of qualitative nature that could complement the evaluation results. With regard to the methodological issues, the approach adopted in this study is based on the mixed method provided through a strategy known as an explanatory sequential project, which enables the choice of an initial exploratory qualitative phase and then continue with the quantitative phase with a larger sample. Thus, in this study the first phase was a semi-structured interview with heads of international universities' offices, which produced information that supported the definition of some constructs of the research instrument that was applied through a survey, representing the second phase of data collection. This survey considered the cross-sectional time perspective that covered the quadrennium from 2013 to 2016 and was applied to the coordinators and professors of stricto sensu postgraduate programs in Administration, totalizing a sample of 51 coordinators and 107 professors. In order to enhance some of the results obtained in the survey, a third phase of data collection was also undertaken, this time through a semi-structured interview with the coordinators of the programs. Among the results obtained, in general, the survey highlights a proposal for classifying a level of internationalization of the programs based on CAPES indicators. Regarding the research hypotheses, the relationship between internationalization efforts (planning, organization and actions) and CAPES indicators was confirmed, however, when tested under moderation of CAPES scoring system, the correlation intensity is only increased from score 3 to 4, but not to score 5. Otherwise the hypothesis related to the reasons for internationalization pointed out by the professors and their relation to CAPES indicators was not confirmed and there is no difference in the correlation intensity due to CAPES score. Finally, when evaluating the results of the three stages of data collection, performed through parametric and non-parametric statistical tests for quantitative data and content analysis for the qualitative data, it was verified that the programs that are close to reach score 6 still present difficulties in progressing with internationalization. Therefore, since internationalization is a requirement in programs 6 and 7, it is recommended that CAPES expands the possibilities of indicators, in this case qualitative ones, so that it is possible to evaluate internationalization in a more comprehensive and gradual aspect, mainly in programs with scores 4 and 5. Consequently, these last ones might possibly be more likely to improve their scores in the future.